Is There an Association Between Social Support and Pain Among Individuals Living With Multiple Sclerosis? - Khrisha B. Alphonsus PhD; Carl D'Arcy PhD (SAGE Publishing, 2021)
Context. Pain is one of the most common symptoms reported by patients living with Multiple Sclerosis (MS). Risk factors associated with pain may include individual's cognitive thinking process, emotional and behavioural response to pain and amount of social support. There is a lack of research on the influence on the amount of social support and its association to pain outcomes. Objective. The primary objective of this study was to determine the association between amount and of social support and its association with odds of pain among individuals with MS. Methods. The Survey on Living with Neurological Conditions in Canada (SLNCC) 2011-2012 linked to the Canadian Community Health Survey (CCHS) 2010-2011 was used to carry out a logistic regression model for this analysis (N = 78,623). Main outcome measures. The factors that were assessed were psychological factors, problems with sleeping, self-perceived general health, self-perceived level of stress, number of years living with MS, as well as social factors. The outcome variable was pain. Results. The amount of social support was found to be significant in that individuals who had 3 or fewer types of social support were 3.02 times more likely (95% CI 1.06 to 8.59) to report being in pain as opposed to individuals who had 4 types of support. The results indicate the importance of self efficacy in overcoming symptoms of MS and the need for more home care services.